Ірраціональні аспекти правової реальності у світлі юридичної антропології - Завальнюк, Володимир Васильович; Завальнюк, Владимир Васильевич; Zaval'njuk, V. (My University, 2013)
The article analyzes the irrational aspects of modern law. Examples of myths in social legal mentality, constitutional and sectoral legislation, legal procedures are revealed. The need to distance from a purely positivist understanding of law as a system of rational rules of conduct is concluded. Irrational aspects of the law are in some cases more powerful than rational.
Завальнюк В. В. Ірраціональні аспекти правової реальності у світлі юридичної антропології / В. В. Завальнюк // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 11-22.
Keywords: ірраціональні аспекти сучасного права; міфологеми у суспільній правосвідомості, законодавстві та правових процедурах; філософія права; иррациональные аспекты современного права; мифологемы в общественном правосознании, законодательстве и правовых процедурах; философия права; irrational aspects of modern law; myths in the public sense of justice, law and legal procedures; philosophy of law